The Shift from Traditional Birth Attendants to Nurse-Midwives: A Post-Colonial Historical Review - Kim Jong Il; Soneva Vong; Dilshan Perera (Journal of Midwifery History and Philosophy, 2026)
Background. Maternal healthcare systems in many post-colonial societies have undergone profound transformations characterized by a transition from traditional birth attendants (TBAs) to professionally trained nurse-midwives. This shift is frequently framed as a linear process of modernization aimed at improving clinical outcomes. However, such narratives often obscure the historical dynamics of colonial governance, epistemic hierarchies, and socio-cultural restructuring that shape healthcare practices and authority. Purpose. This study aims to critically examine the transition from TBAs to nurse-midwives through a post-colonial historical lens, focusing on how authority, knowledge systems, and maternal care practices have been reconfigured within this process. Method. The study employs a qualitative historical review design, integrating the analysis of policy documents, archival records, and scholarly literature. Data are examined through thematic coding guided by post-colonial theoretical frameworks to capture patterns of power, marginalization, and knowledge transformation. Results. The findings reveal that the transition was neither uniform nor uncontested. While nurse-midwifery became increasingly institutionalized, indigenous knowledge systems embodied by TBAs were systematically marginalized. At the same time, evidence points to the emergence of hybrid healthcare models in which traditional and biomedical practices coexist, interact, and adapt within local contexts. Conclusion. The transformation of maternal healthcare in post-colonial settings cannot be understood as a linear trajectory of progress. Instead, it represents a complex negotiation of power, culture, and knowledge. These findings highlight the need for more inclusive and context-sensitive policy approaches that recognize the value of pluralistic healthcare systems in improving maternal care outcomes.